The spectrum of building block conformers sustains the biophysical properties of clinically-oriented self-assembling protein nanoparticles - Voltà Durán, Eric (2022)
Histidine-rich peptides confer self-assembling properties to recombinant proteins through the supramolecular coordination with divalent cations. This fact allows the cost-effective, large-scale generation of microscopic and macroscopic protein materials with intriguing biomedical properties. Among such materials, resulting from the simple bioproduction of protein building blocks, homomeric nanoparticles are of special value as multivalent interactors and drug carriers. Interestingly, we have here identified that the assembly of a given His-tagged protein might render distinguishable categories of self-assembling protein nanoparticles. This fact has been scrutinized through the nanobody-containing fusion proteins EM1-GFP-H6 and A3C8-GFP-H6, whose biosynthesis results in two distinguishable populations of building blocks. In one of them, the assembling and disassembling is controllable by cations. However, a second population immediately self-assembles upon purification through a non-regulatable pathway, rendering larger nanoparticles with specific biological properties. The structural analyses of both model proteins and nanoparticles revealed important conformational variability in the building blocks. This fact renders different structural and functional categories of the final soft materials resulting from the participation of energetically unstable intermediates in the oligomerization process. These data illustrate the complexity of the Hismediated protein assembling in recombinant proteins but they also offer clues for a better design and refinement of protein-based nanomedicines, which, resulting from biological fabrication, show an architectonic flexibility unusual among biomaterials.